Elektroniczny warsztat informacyjny w bibliotekach akademickich na przykładzie Biblioteki Uniwersytetu Łódzkiego i Biblioteki Politechniki Łódzkiej – organizacja i obszary współpracy - Leder-Niewola , Beata; Sójkowska, Iwona (Acta Universitatis Lodziensis. Folia Librorum, 2009)
The areas of cooperation of two biggest Lodz academic libraries – University of Lodz Library (BUŁ) and Technical University of Lodz Library (BPŁ) are discussed in the article. The two libraries have cooperated unofficially since the moment of coming into existence, especially in the field of user services. The University of Lodz Library offers the 2 million book collection and electronic reference resources in humanities and arts. The Technical University of Lodz Library makes information in science, technique and technology available; in a print form and as abstract and full text electronic services. Nowadays the cooperation of the two libraries is based on the electronic reference resources, further detailed information included in the article. The authors discussed the characteristic features of information resources of each library and the role of librarians in electronic reference resources promotion.